Analysis of Numberblocks Youtube Videos on Children’s Acquisition of Numbers - Ni'fatul Fauziyah; Lies Amin Lestari; Ahmad Munir (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2025)
The aim of this study was to analzye the contents Youtube videos called Numberblocks on children’s acquisition of numbers. Numberblocks videos have the highest scores on the content analysis which are the accuracy, age-appropriateness, engagement, and repetition (score = 5) with the lowest scores on pedagogical approaches: real-world connections (score = 3) and interactivity (score = 1). The average score of the linguistic analysis is 4.15 with the lowest score on the language clarity especially on the pace of speech. Numberblocks videos have the perfect average score 5 on the presentation analysis. And in the visual analysis, numbers are mostly represented in various ways (score = 4,5) but real-world examples are rarely used to illustrate number concepts (score = 2,5). It can be concluded that Numberblocks videos are successful to drag young learners’ concept of numbers into the blocks and this helps their acquisition with numbers. However, parents' guidance is needed so that young learners will have more interaction and correlate the idea into real world situations and examples.